Recent Developments and Achievements in Biocybernetics and Biomedical Engineering Proceedings of the 20th Polish Conference on Biocybernetics and Biomedical Engineering, Kraków, Poland, September 20-22, 2017 (Advances in Intelligent Systems and Computing,, 2018)
This book presents the best 27 papers from the 20th Polish Conference on Biocybernetics and Biomedical Engineering (PCBBE) hosted by the AGH University of Science and Technology in Krakow. This biannual event has been held for nearly four decades and offers scientists and professionals from the fields of engineering, medicine, physics, and computer science an excellent platform for exchanging ideas. Biocybernetics and biomedical engineering is currently considered a promising approach to improving healthcare - and consequently quality of life. Innovative technical solutions not only respond to the needs of caregivers, but also stimulate the development of medical sciences by supporting medical practitioners, and we are currently witnessing a profound change of the role of medicine that has become ubiquitous in everyday life thanks to recent technological advances. The development of civilization manifests itself in a growing focus on investigating the secrets of the human life, continuous efforts to support life, and mimicking biological systems in engineering. Presenting the latest developments in all areas of biomedical engineering, the book is a valuable resource for researchers and scientists in the field.